Learning to Learn : by knowing your brain. A guide for young students - Martin, Héctor Ruiz, ....- (Brighton : International Science Teaching Foundation, 2020)
Why do some people excel in their studies more than others? What differences among students determine their ability to learn? How can we achieve deeper, long-lasting, and transferable knowledge to new situations? These are questions of great interest that neuroscience and cognitive sciences have investigated in recent decades. Their findings are as surprising as they are encouraging: the learning strategies we employ can make a difference in our efforts. Revealing these strategies based on scientific evidence is precisely the purpose of this book.
Keywords: Cognitieve psychologie